Effectiveness of acupuncture treatment for stroke and stroke complications: a protocol for meta-analysis and systematic review based on randomized, single-blind, controlled trials - Wang, Xiao-Yu; Liu, Wei; Li, Huan; Rong, Meng-Ying; Li, Jing-Yu; Wang, Shao-Kang; Du, Yu-Zheng; Zhao, Qi (Frontiers in Neurology, 2023)
Introduction The treatment and rehabilitation of stroke and its complications have become major global health issues. Acupuncture is widely used as a complementary and alternative treatment for stroke. Many clinical studies have evaluated the efficacy and safety of acupuncture, but the research results need to be more consistent. The quality of research based on previously published meta-analyzes is uneven, leading to unstable conclusions. This study aims to provide a comprehensive and systematic analysis of the efficacy of high-quality, randomized controlled trials (RCTs) based on blinded designs for treating stroke and its complications. It also aims to review the characteristics of blinded designs and the current use of sham/placebo acupuncture controls in treating stroke. Methods and analysis This study will be conducted under the reporting guidelines for systematic reviews and meta-analyzes. Randomized controlled trials using acupuncture as the primary measure for stroke will be searched in databases such as China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), Wan-fang, PubMed, Embase, Cochrane Library, and Web of Science. To evaluate high-quality research based on a blind design, if the trial evaluates the efficacy of any acupuncture intervention by including a sham/placebo acupuncture control, it will be included. The primary outcome indicator will be the ability to perform daily activities. Secondary outcome indicators include evaluating quality of life and related functions in stroke-related sequelae. We will assess the quality of evidence, reporting quality, and risk of bias for the acupuncture intervention in the literature included in this study using the GRADE system, the STRICTA 2010 checklist, and ROB2.0, respectively. RevMan 5.4 software will be used to conduct the meta-analysis, and Stata 15.0 software will be used for sensitivity analysis and publication bias testing. Discussion By analyzing high-quality, well-designed, randomized controlled trials of acupuncture, the results of this study may contribute to a more objective and standardized evaluation of acupuncture efficacy in treating stroke and its complications. Systematic review registration: PROSPERO, Identifier (CRD42023378930).